Democratising hospital design: Reconfiguration of disciplinary power via M. Foucault’s theory - Zhao, Ke; Kosenko, Danylo (Art and Design, 2026)
Hospital interiors remained decisive sites where spatial form, materials, lighting, and acoustics structured everyday conduct, making the democratisation of design a timely concern for healthcare quality and dignity. The purpose of this study was to theorise and test a “democratisation design” logic that reconfigured disciplinary power into emancipatory spatial practice. A mixed qualitative design method was employed that combined literature synthesis, discourse analysis of briefs and standards, and comparative case studies of five contemporary hospitals to evaluate spatial layout, material language, adjustable lighting, and participatory navigation. How traditional interiors encoded hierarchy through radial zoning, cold hard finishes, uniform high-illuminance lighting, and voice-controlled soundscapes was investigated; these configurations produced routinised flows and asymmetric visibility. Decentralised layouts, nature-based materials, and circadian-tuneable lighting were established to rebalance perception and privacy while sustaining hygiene and throughput. Dialogic interfaces – open corridors, shared decision-making corners, and self-service information – were analysed and were found to reduce information asymmetry, improve perceived control, and increase trust and satisfaction. The findings were summarised as a four-part framework (movement, material, light, sound) showing where specific interventions reinforced or redistributed power across entry, waiting, and treatment zones; across five cases, queuing stress was reduced, wayfinding times were shortened, and staff coordination was supported without increasing infection-control risk or compromising clinical workflows. The results could be used by healthcare architects, engineers, and hospital managers to inform design guidelines and post-occupancy evaluations that align safety and efficiency with agency, dignity, and participation in both new builds and phased renovations